Are Friday announcements special? Overcoming selection bias - Michaely, Roni; Rubin, Amir; Vedrashko, Alexander (Journal of Financial Economics, 2016)
We report reduced market response to Friday announcements of dividend changes, seasoned equity offerings, share repurchases, earnings, and mergers, which is seemingly consistent with the notion of investor inattention on Fridays. However, we show that these findings are an outcome of selection bias. Firms that make announcements on Fridays experience reduced market response on any weekday and have common unobserved characteristics across announcement types. After correcting for selection bias, there is no evidence that investors pay less attention to announcements made on Fridays. The method introduced here is applicable to other studies in which an exogenous factor influencing firm performance can actually be associated with firm characteristics.